2016
DOI: 10.1186/s13059-016-1030-0
|View full text |Cite
|
Sign up to set email alerts
|

An epigenetic clock analysis of race/ethnicity, sex, and coronary heart disease

Abstract: BackgroundEpigenetic biomarkers of aging (the “epigenetic clock”) have the potential to address puzzling findings surrounding mortality rates and incidence of cardio-metabolic disease such as: (1) women consistently exhibiting lower mortality than men despite having higher levels of morbidity; (2) racial/ethnic groups having different mortality rates even after adjusting for socioeconomic differences; (3) the black/white mortality cross-over effect in late adulthood; and (4) Hispanics in the United States havi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

67
575
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 594 publications
(653 citation statements)
references
References 88 publications
67
575
10
1
Order By: Relevance
“…In comparison, DNAm Δage was previously shown to be associated with all‐cause mortality, but not with prevalent CHD or hypertension (Marioni et al ., 2015; Horvath et al ., 2016). mRNA Δage was reported to be associated with blood pressure, glucose, and HDL and total cholesterol, but not with all‐cause mortality (Peters et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, DNAm Δage was previously shown to be associated with all‐cause mortality, but not with prevalent CHD or hypertension (Marioni et al ., 2015; Horvath et al ., 2016). mRNA Δage was reported to be associated with blood pressure, glucose, and HDL and total cholesterol, but not with all‐cause mortality (Peters et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The resultant DNA methylation‐based predicted age ( i.e ., DNAm age) was associated with chronological age in several independent studies. The difference between DNAm age and chronological age ( i.e ., DNAm Δage) has been proposed as an index of accelerated aging and was reported to be associated with all‐cause mortality and several coronary heart disease risk factors (Marioni et al ., 2015; Christiansen et al ., 2016; Horvath et al ., 2016). …”
Section: Introductionmentioning
confidence: 99%
“…For example, aging is a crucial risk factor for cancer [72,73] and also relevant to the treatment outcome [74]. Studies have shown that the epigenetic age of human tissues can be defined by the methylation level of 353 CpG sites, which are termed clock CpGs [75], and that the epigenetic aging rates are significantly associated with ethnicity [76]. Here we discuss whether CpG sites related to the drug response or ADME would be affected by both the ethnic difference and the epigenetic age difference.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in single cell 'omics' provide a more complex picture of identity, often revealing continuums of multiple facets of cellular plasticity [47]. Therefore, the distinction between DNA methylation changes at single loci within a canonical cell type (intrinsic in Horvath's definition [19]) and changed cell fate characterized by DNA methylation changes at multiple loci (extrinsic by Horvath's definition) is just one of scale. How do we define where variation within a specific cell subtype ends and a new cellular fate begins?…”
Section: What Is a Cell Type Anyway?mentioning
confidence: 99%
“…For instance, if all B cells are methylated at a particular locus, while all other cellular constituents of blood are not, variations in the methylation signal at this locus will reflect (at least in part) the proportion of B cells in a blood sample ( Figure 1B). Horvath et al [19] recently referred to DNA methylation change due to change in cellular proportions as the 'extrinsic' signal. Horvath et al also defined an intrinsic signal as that occurring only within a canonical cell type ( Figure 1C).…”
Section: Dna Methylation Marks Integrate Genetic and Environmental Inflmentioning
confidence: 99%